« No ifs or buts. / I didn’t say if or but, I said no » : Le sujet et son désir contre le discours de la psychiatrie - Nicolas Pierre Boileau (Sillages Critiques)
Sarah Kane’s oeuvre enables us to see how the body, which was initially foregrounded in her work, gradually disappears. The body that was once abused, exposed, mistreated in Blasted, to the extent that it was unbearable in performance, is reduced to a voice, in 4.48 Psychosis, whose language defies the laws of grammar and which seems to circulate like a bodiless soul. This article seeks to interpret the gradual disappearance of the body on stage as a questioning of the clinical construction of the subject, and an attempt at representing it as a subject of language, against cognitive psychology. The aim is to show how madness evolves from a theoretical construction in which it is a deviation from normalcy to a discourse that construes it as a response to the real, as defined by J. Lacan.